USSR Report, USA: Economics, Politics, Ideology - JOINT PUBLICATIONS RESEARCH SERVICE ARLINGTON VA (1987)
PARTIAL CONTENTS: The Democrats After the Elections; Prospects for Soviet-American Cooperation (A Physician's Point of View); U.S. Transnational Banks in the 80's; Washington's View of the Rarotonga Treaty; In the American Schools; The Consequences of the Iranian Affair; The Pentagon and Austrian Neutrality; The Canadian Economic Situation in the 80's; 'This Is a Special Moment in Your History'; Re-Inventing the Corporation (Continued); Organization and Administration of SDI Program; Yukon; Northwest Territories; U.S. Industrial Espionage.